Feelings experienced in hyperbaric oxygen therapy: the users’ voice - Machado, Maria Samya Carvalho; Carvalho, Evanilda Souza de Santana; Paranhos, Rayssa Fagundes Batista; Costa, Cintia Silva de Souza (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objetive: To characterize the feelings experienced by users of hyperbaric oxygen therapy (HBOT). Methods: Qualitative study, usingmultiparametric techniques for data collection such as the free word association technique, drawing-and-story procedure with theme and the semistructured interview. For the analysis, the discursive material, together with the visualization of the drawings and the responses of the word-free associations, was cross-referenced and the method of content analysis was employed, thus allowing the feelings experienced at HBOT to be portrayed. Results: The categories emerged: fear and anxiety; feeling of imprisonment and tiredness; happiness and confidence/hope, the latter being subdivided into trust in the therapy and in God. Conclusion: After, the first sessions and especially after the guidance and incentives from the professionals, the negative feelings were softened and gave way to satisfaction, followed by happiness in being able to return to family and social life and all this anchored in the feeling of hope and faith.